Analysis of concrete beams with circular web openings using strut and tie models - Mansur, M. A.; Tan, King Hwee; Weng, W. (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2006)

(untitled)
This study examines the strut-and-tie model for the analysis of reinforced concrete beams that contain geometric discontinuities in the form of a transverse circular opening in the web. Three T-beams with circular openings tested earlier by the authors have been chosen, and a strut-and-tie model was constructed for each beam. A comparison of the theoretical predictions concerning the ultimate strength, mode of failure and the proportion of applied shear carried by the chord members above and below the opening show good agreement with test results. The truss model also explains clearly the role of diagonal reinforcement in relieving concrete distress at the throat section by transferring a significant amount of applied shear across the discontinuity.